Otimização multiobjetivo do despacho térmico para sistemas integrados de energia considerando diferentes patamares da carga complementar - Hammerschmitt, Bruno Knevitz (2022)
The complexity of integrated energy systems, with centralized load and generation, generally results from their operation, coordination and planning. In addition, an electric system with multiple energy generation sources requires some planning for each source dispatch, in order to protect themselves with energy reserves and keep the system with uninterrupted supply and reliable within security limits. Aiming decarbonize the energy matrix most electrical systems are undergoing a transition with renewable resources and at full expansion. However, these technologies have the characteristics of being intermittent and stochastic. In view of this, energy sources with a controllable power generation, generally coming from energy resources of a fossil nature, become necessary to accommodate the generation inconstancy from intermittent renewable sources, also to complement the load demand requests due to the unavailability of other energy sources. For this, multi-energy systems for electric energy generation need tools for the dispatch optimization of controllable energy sources, as well as for the systems evaluation and adequacy in face of the seasonal variations of the energy generation and the load demand. Therefore, this work aims to develop a multi-objective optimization model for short-term thermal dispatch, following the capacity constraints of the Thermal Power Plants (TPPs) and based on the minimum cost, by the model Non-dominated Sorting Genetic Algorithm-III (NSGA-III). To achieve the proposed objective, it was necessary to adapt the system with the adjustment of the base energy generation, coming from renewable energies. For this, a method of adjusting the base energy data was developed to reduce the complementary energy climb, restricting to the flexible thermal power limit. Then, the complementation by thermal energy was carried out, applying the NSGA-III model to obtain the best arrangements of the thermal dispatch, considering the levels of base, intermediate and peak complementary load, observing the capacity limits and at minimum cost. Additionally, an upper limit of reserve energy was proposed, as a precaution for emergencies. With this, from the lowest cost arrangement, the thermal dispatch was performed considering the fully meet of the system complementary load. The results obtained reduced the TPPs idleness, maximized the thermal dispatch of the renewable energy sources, and still made viable the system operational flexibility. Thus, this work allows the thermal dispatch optimization in the short-term, and can also help in planning studies of multi-energy systems.